A new synonym in Pantropical Aspilia (Ecliptinae, Heliantheae, Asteraceae) - Alves, Maria; Roque, Nádia (Phytotaxa, 2018)
Currently there are two distinct concepts for Aspilia Thouars (1806: 12) and Wedelia Jacq. (1760: 28) (Ecliptinae, Heliantheae, Asteraceae). The first concept separates Aspilia and Wedelia by neutral ray flowers vs. fertile ray flowers, respectively (Candolle 1836, Bentham 1873, Baker 1884). This concept was adopted by Santos (2001) who added the presence of a scar at the base of cypselae in Aspilia of Brazil (vs. its absence in Wedelia), a taxonomic position followed by the Brazilian researchers (BFG 2015, Alves & Roque 2016, Silva & Teles 2017, Flora do Brasil 2020 under construction). The second concept considers only Wedelia as a valid genus encompassing all Aspilia species (Strother 1991, Robinson 1992, Turner 1992, Panero 2007). Studies of molecular phylogeny are being conducted in the Aspilia and Wedelia complex in order to recover monophyletic groups (Alves in prep) and for this, new nomenclatural arrangements are required as follow below.